Analisis Kalsium (Ca) pada Ikan Petek dan Mujair dengan Metode Kompleksometri - Adriani, Azmalina; Fauziah, Fauziah; Saputra, Riki (Oceana Biomedicina Journal, 2019)
Fish is one ofthe example of a comestibles that contains a lot of protein and minerals, one of which is calcium. Calcium functions for the body's metabolism in the bone and tooth formation. Petek and Mujair fish contain calcium that is needed by the human body. The purpose of this study was to determine the levels of calcium contained in Petek and Mujair fish. The sampling was done by purposive sampling, which the sample used was obtained by the market in the Peunayong Banda Aceh. This research used complexometry methods. The samples of Petek and Mujair fish that had been cleared were titrated using Na2-EDTA as the titrator. The result showed that Petek and Mujair fish had different calcium levels where the calcium levels in Petek fish reach an average of 0.853% and the calcium levels in Mujair fish reach an average of 0.616%. Petek fish had higher calcium levels than Mujair fish, it was caused by their habit, where Petek fish was sea fish that contained fat, vitamins and minerals, while Mujair fish was freshwater fish that contained carbohydrates and proteins.Keywords: Calcium, Petek fish, Mujair fish, Kompleksometry.